The Effect of Using Flexible Grouping Strategy in Accordance with the Kinesthetic Training in Learning Some Football Skills - Ismail, Saad Amir; Hussein, Hussein Ali; Radhi, Imad Tu'ma (International Journal of Psychosocial Rehabilitation, 2020)
The research includes the definition, introduction and importance of research which is that a teacher who is fluent in the use of different strategies and methods during teaching is the one who makes the lesson characterized by flexibility and vitality, produced by his own style and reflected on the learners making them interact with the lesson through good performance of the exercise and the output of learning unit in line with the learners level and abilities which in turn gives an advantage in learning those sport skills. Football, which is one of the team games characterized by high attention to the teammate, opponent and ball, needs, to some extent, high degrees of kinetic, skill and physical abilities, and the contact with the opponent team, thus it requires composite exercises, especially in terms of sense and perception of distance and time. Thus, the importance of research is evident in that the teacher uses the strategy of flexible grouping in teaching and the introduction of kinesthetic exercises that develop the learner's abilities of football and affect skills stimulation and learning.The problem of the research lies in the fact that the researchers, through their work as teachers and their field trips to schools during the periods of application, have found that physical education teachers lack the change and the identification of the new teaching methods strategies and means, as well as the weakness in students towards motor perception and sense and the way of learning them, which motivated the researchers to stand on this real problem, study and provide a solution to it, which is through the use of flexible grouping strategy in accordance with the kinesthetic exercises in learning some skills in football.The objectives of the research included:• Developing learning modules using the flexible grouping strategy according to kinesthetic training to learn some skills in football.• Identifying the impact of using the flexible grouping strategy in accordance with the kinesthetic exercises in learning some football skills.The research used an experimental method, and its sample consisted of 60 high school students of the fifth literary class. It also included the tests used in the research, pilot study, pre-tests, the application of learning modules on the research sample and the post-tests. As well as the presentation, analysis and discussion of the pre- and post-results between the experimental and control groups and skills post-tests between the two groups.